Analisis Kinerja Kualitas Jaringan 4G LTE Di Kawasan Perumahan Singgalang, Koto Tangah, Kota Padang - Rahmat, Fauzi Aditia (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2022)
The most widely used mobile technology today is 4G LTE. In the development of 4G LTE technology, there are still many problems related to network performance due to the increasing number of users and the poor quality of coverage areas. From previous studies, only checking the quality of the network without conducting further improvement analysis. For this reason, it is necessary to analyze network quality performance and conduct network repair analysis in the area. To find out the quality of the network, it is necessary to take data in the field, the method used is the Drive Test method. From the results of the drive test, it was found that 60.85% of the 411 samples were in the bad category, causing many areas to experience bad spots. In this area, bad spots occur due to interference between site PAD018ML_Ganting Tabing and Site PAD192ML_Kuala Niur, as well as the distance between Site PAD018ML_Ganting Tabing and User Equipment is quite far and there is no cell serving from the nearest site in the area. That way it results in some areas experiencing poor network quality. From the analysis of area repair is carried out re-azimuth to correct the poor quality of tissues.